A Layered–Tunnel Intergrowth Structure for High‐Performance Sodium‐Ion Oxide Cathode. Issue 22 (27th May 2018) - Xiao, Yao; Wang, Peng‐Fei; Yin, Ya‐Xia; Zhu, Yan‐Fang; Yang, Xinan; Zhang, Xu‐Dong; Wang, Yuesheng; Guo, Xiao‐Dong; Zhong, Ben‐He; Guo, Yu‐Guo
Abstract: Delivery of high‐energy density with long cycle life is facing a severe challenge in developing cathode materials for rechargeable sodium‐ion batteries (SIBs). Here a composite Na0.6 MnO2 with layered–tunnel structure combining intergrowth morphology of nanoplates and nanorods for SIBs, which is clearly confirmed by micro scanning electron microscopy, high‐resolution transmission electron microscopy as well as scanning transmission electron microscopy with atomic resolution is presented. Owing to the integrated advantages of P2 layered structure with high capacity and that of the tunnel structure with excellent cycling stability and superior rate performance, the composite electrode delivers a reversible discharge capacity of 198.2 mAh g −1 at 0.2C rate, leading to a high‐energy density of 520.4 Wh kg −1 . This intergrowth integration engineering strategy may modulate the physical and chemical properties in oxide cathodes and provide new perspectives on the optimal design of high‐energy density and high‐stable materials for SIBs. Abstract : A novel layered–tunnel intergrowth structure with stoichiometric Na0.6 MnO2 composition is designed as a high‐performance cathode for sodium‐ion batteries (SIBs). Owing to the integrated advantages of the P2 layered structure with high capacity and that of the tunnel structure with excellent cycling stability and superior rate performance, this intergrowth cathode might be a promising cathode candidate for the large‐scale energy storage application of SIBs.